ФОРМУВАННЯ У СТАРШОКЛАСНИКІВ НАВИЧОК САМООСВІТНЬОЇ МУЗИЧНОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2006)
In articles the problem of self-educational activity of schoolboys is examined during training to bases of music and a role of the teacher m her organization.